Asthma and Atopy in Children Born by Caesarean Section: Effect Modification by Family History of Allergies - a Population Based Cross-sectional Study - Middleton, Nicos; Kolokotroni, Ourania; Lamnisos, Demetris; Gavatha, Marina; Priftis, Kostas N.; Yiallouros, Panayiotis K. (My University, 2012)
Background: Studies on the association of birth by caesarean section (C/S) and allergies have produced conflicting findings. Furthermore, evidence on whether this association may differ in those at risk of atopy is limited. This study aims to investigate the association of mode of delivery with asthma and atopic sensitization and the extent to which any effect is modified by family history of allergies.Methods: Asthma outcomes were assessed cross-sectionally in 2216 children at age 8 on the basis of parents' responses to the ISAAC questionnaire whilst skin prick tests to eleven aeroallergens were also performed in a subgroup of 746 children. Adjusted odds ratios of asthma and atopy by mode of delivery were estimated in multivariable logistic models while evidence of effect modification was examined by introducing interaction terms in the models.Results: After adjusting for potential confounders, children born by C/S appeared significantly more likely than those born vaginally to report ever wheezing (OR 1.36, 95% CI 1.07-1.71), asthma diagnosis (OR 1.41, 95% CI 1.09-1.83) and be atopic (OR 1.67, 95% CI 1.08-2.60). There was modest evidence that family history of allergies may modify the effect of C/S delivery on atopy (p for effect modification=0.06) but this was not the case for the asthma outcomes. Specifically, while more than a two-fold increase in the odds of being a topic was observed in children with a family history of allergies if born by C/S (OR 2.62, 95% CI 1.38-5.00), no association was observed in children without a family history of allergies (OR 1.16, 95% CI 0.64-2.11).Conclusions: Birth by C/S is associated with asthma and atopic sensitization in childhood. The association of C/S and atopy appears more pronounced in children with family history of allergies.
Keywords: Asthma; Vaginal delivery; Caesarean section; Wheeze; Atopic sensitization; Child